Febre tifóide: perfil clínico-epidemiológico e de sensibilidade das cepas de Salmonella Typhi a antimicrobianos no Hospital Universitário João de Barros Barreto - PINTO, Daniel Fagner O' de Almeida (2023)
Typhoid fever is an infectious disease of world-wide distribution narrowly related to the low partner-economic levels, the bad conditions of hygiene and the deficiency in the treatment and the distribution of the water, occurring more frequently in the developing countries. For a long time the chloramphenicol was adopted as drug of choice in the treatment of the patients with this illness in the University Hospital João de Barros Barreto (HUJBB), however, in the recent years, this drug, following a global trend, by the appearance of serotypes of Salmonella typhi multidrug-resistant, is being substituted for fluoroquinolones, more specifically by ciprofloxacin. In view of the high cost of the treatment with ciprofloxacin in comparison to the first drug, the analysis of the profile of susceptibility becomes a great importance for the election of an antimicrobials that presents a better cost-benefit, becoming thus, more able to the the reality of the public health system. The present work aims to analyze the profile of susceptibility of serotypes of Salmonella typhi to antimicrobialses in 36 patients with typhoid fever registered in the HUJBB in the period of 2001 up to 2006. For such, an evaluation questionaire was elaborated where they had been compared the gender, age at the diagnosis, occupation, scholarship, naturalness, city of origin, . Also the presented time of evolution of the illness before the search for medical care, signals and symptoms. The statistical analyses had been carried through by means of the program Bio Estat version 3.0, applying the test of the qui-square and the significance statistics was accepted to the 95% level. The results had allowed them to conclude that: the age band more affected is of the young adults, with predominance of the masculine gender (63,9%), the majority of the cases was from the region metropolitan of Belém (72,23%) and occurred in the second half of the year favoreted by geo-climatic and cultural factors, presented low scholarship, the symptom most frequent was the fever. The most used antibiotic during the treatment was the ciprofloxacin (72,23%). There weren’t resistance cases. The great majority of the patients evolves with the remission of the symptoms, but 77,78% did not return for the accomplishment of a complete control of cure.